Gait Analysis of Walking Locomotion Enhanced by an Impedance-Controlled Gait-Aid Walker-Type Robot - Watanabe, Shun; Tsumugiwa, Toru; Yokogawa, Ryuichi (IEEE/SICE International Symposium on System Integration, 2020)
In this study, we conducted gait analysis of walking locomotion enhanced by an impedance-controlled gait-aid walker-type robot. The purpose of this study was to clarify the effect of different impedance parameters set of the robot on the movement of the lower extremity joints and the muscle activity of the lower extremities. The experimental results show that there is a significant difference in the maximum knee joint extension angular velocity during the swing phase without movement restriction, and there is a significant difference in the muscle activity of the tibialis anterior under right knee joint flexion restriction using an orthosis to restrict the flexing and extending movement of the knee joint. We revealed that the difference in damping coefficient of the impedance parameters set of the robot changes the subject's gait pattern.